Orbital myocysticercosis: a rare case report - Lahkar, Gariyashee; Rajendra Nath Gogoi,; Naveen Kumar, (International Journal of Research in Medical Sciences, 2023)
We describe a case of ocular myocysticercosis in a 26-year-old male patient, who presented with sudden onset proptosis of the right eye and double vision for 8 days with no history of trauma. MRI showed well defined peripherally enhancing intraconal lesion suggestive of myocysticercosis in inferior rectus muscle. On administration of low dose oral steroids followed by anthelminthic medications, patient showed marked resolution of symptoms.